Differences in gonadotropin-releasing hormone-induced calcium signaling between melatonin-sensitive and melatonin-insensitive neonatal rat gonadotrophs - Zemková, H; Vanecek, J (Endocrinology, 2000)
The sensitivity of GnRH-stimulated calcium signaling to melatonin, in a subpopulation of neonatal gonadotrophs, is supposed to be attributable to melatonin receptors. However, it is not yet known whether the intracellular pathway for GnRH action in melatonin-sensitive cells is the same as in melatonin-insensitive cells. By monitoring intracellular Ca2+ changes as an outward current carried through apamin-sensitive Ca2+-activated K+ channels, we compared GnRH-induced calcium responses in these two subpopulations of neonatal gonadotrophs. GnRH induced various oscillatory, as well as nonoscillatory, responses in both cell types that was not related to melatonin sensitivity. Melatonin-sensitive GnRH-induced responses could be clearly distinguished according to the pharmacological properties of their latency. The latency increased in zero extracellular Ca2+ or with the addition of nifedipine, staurosporine, and ryanodine. This effect was only rarely observed in melatonin-insensitive cells. This indicates that there are two pathways for initiation of GnRH-induced calcium signaling in neonatal gonadotrophs. The first pathway is mediated by inositol 1,4,5,-trisphosphate production, whereas the second involves extracellular calcium entry through voltage-dependent L-type Ca2+ channels, protein kinase C activation, and Ca2+ release from a ryanodine-sensitive store, which may coactivate Ca2+ release from an inositol 1,4,5,-trisphosphate-sensitive store. Only the second mechanism is accessible to inhibition by melatonin.
Keywords: hypofýza; Pituitary Gland; membránové potenciály; Electrophysiology; metoda terčíkového zámku; Rats; Animals, Newborn; inhibitory fosfodiesteras; Calcium Channel Blockers; Antioxidants; apamin; Staurosporine; vápník; Calcium Signaling; Type C Phospholipases; elektrofyziologie; Gonadotropin-Releasing Hormone; Phosphodiesterase Inhibitors; novorozená zvířata; Patch-Clamp Techniques; Membrane Potentials; hormon uvolňující gonadotropiny; staurosporin; krysa rodu Rattus; antioxidancia; blokátory kalciových kanálů; Calcium; nifedipin; ženské pohlaví; vápníková signalizace; zvířata; fosfolipasy typu C; Melatonin; ryanodin; Potassium Channels; melatonin; draslíkové kanály; Nifedipine; Apamin; Female; Ryanodine; Enzyme Inhibitors; inhibitory enzymů; Animals